Argumentation, Cooperation, and Disagreement - Bernache Maldonado, Fabian (Informal Logic, 2025)
To get a better comprehension of the nature of argumentation, we need to understand the context in which this practice produces its particular benefits. I hold that this context consists basically in the presence of two conditions: 1) the need for cooperation, and 2) the possibility of dissent. I argue that contributing to the coordination of collective action is the particular benefit argumentation is able to produce in this context and that obtaining this benefit constitutes its main function. Thus, the main function of argumentation is not epistemic. Truth is important when we argue, but epistemic improvement is not the main aim of argumentation, even if this benefit may be a common result of it.